DEVELOPMENT OF A QR CODE-BASED PRACTICAL GUIDEBOOK FOR THE INTERNSHIP COURSE IMPLEMENTATION OF INDEPENDENT LEARNING FOR COMMUNITY EDUCATION STUDENTS - Shomedran, Shomedran; Nurrizalia, Mega; Helmi, Henny; Maryani, Maryani (Universitas Muhammadiyah Mataram, 2025)
The aim of this research is to develop a QR Code-based practical guidebook for internship courses for students of the Public Education Study Program, FKIP, Sriwijaya University, looking at its validity and practicality. This research uses a type of development research with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. Through certain considerations, this research was carried out in only 4 (four) stages. Data collection was carried out using questionnaires and documentation methods. The research results showed that at the analysis stage, respondents needed a QR Code-based internship practice guidebook. Data collection was carried out using questionnaires and interviews. The results of the development showed a percentage of 75% with a valid category for Indonesian language experts, then the validation of material experts obtained a score of 92.5% which means very good and valid, then the results of the media expert validation obtained a score of 97.5% which means also very good, from three validators an average score of 88.33% was obtained which means the product is valid. Furthermore, the results of the product trial for one to one obtained a score of 100%, meaning it is very practical, then the results of the small group trial obtained a score of 99.75% which means it is very practical. Based on these results, the study concludes that the PLS internship practice guidebook media based on Qr Code can be said to be practical and can be implemented to students of Community Education, FKIP, Sriwijaya University.